Amit Ambalal. Krishna as Shrinathji; Rajasthani Paintings from Nathvara. Nueva York e India: Mapin Internacional Inc. Chidambaram Ahmemdabad, 1987. 177 pp. - Thukral, Uma (Estudios de Asia y África, 1996)
-